1990
DOI: 10.1111/j.1600-0528.1990.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury excretion and occupational exposure of dental personnel

Abstract: At the annual congresses of the Norwegian Dental Association in 1986 and 1987 surveys were conducted to assess the significance of potential sources of mercury exposure. Morning urine samples and questionnaires were collected from 672 participants in 1986 and 273 participants in 1987. The mean values of the urinary mercury excretion were 39 nmol/L (SD = 29) in 1986, and 43 nmol/L (SD = 36) in 1987. The excretion values were correlated to the answers on questionnaires supplied from each participant. The data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 8 publications
3
11
0
4
Order By: Relevance
“…Failure to detect statistical significance for pubic hair, fingernail, and toenail mercury concentrations may be related to the relatively low numbers of samples collected (100 to 200). This gender difference has been documented in previous surveys, 11,12 in which urine samples were predominantly monitored. A gender-based variation in the renal handling of mercury was proposed as a possible explanation, however, the samples collected in the present survey were of hair and nail making this explanation unlikely.…”
Section: Discussionsupporting
confidence: 54%
“…Failure to detect statistical significance for pubic hair, fingernail, and toenail mercury concentrations may be related to the relatively low numbers of samples collected (100 to 200). This gender difference has been documented in previous surveys, 11,12 in which urine samples were predominantly monitored. A gender-based variation in the renal handling of mercury was proposed as a possible explanation, however, the samples collected in the present survey were of hair and nail making this explanation unlikely.…”
Section: Discussionsupporting
confidence: 54%
“…A lower or no exposure in this group of practitioners may result from more modern standards of dental practice. Naleway C et al [9] Nilsson B et al [10] Langan DC et al [6] Herber RFM et al [11] Jokstad A [12] Martin MD et al [4] Langworth S et al [13] Rojas M et al [14] Millán MAP et al [15] Ritchie KA et al [16] IJOMEH 2007;20(2)…”
Section: Discussionmentioning
confidence: 99%
“…To assess low-level occupational mercury exposure of dental staff, urine mercury (Hg-U) concentration was used as an exposure index [4,[6][7][8][9][10][11][12][13][14][15][16]. The recent literature data confi rm that Hg-U remains the most practical and sensitive marker of monitoring low-level occupational exposure to inorganic mercury [7].…”
Section: Ijomeh 2007;20(2) 148mentioning
confidence: 99%
“…Important factors that may influence exposure and, thus, also the levels of mercury in urine include: (i) the use of a textile rag to squeeze out excess mercury, (ii) the number of years a clinic has used the same premises, (iii) the number of amalgam treatments per week, (iv) whether a mercury spill has occurred in the clinic, and (v) whether Dentomat or capsules were used (4,5,10,11,13,25).…”
Section: Mercury In Dental Amalgam and Determinants Of Exposurementioning
confidence: 99%
“…One of the main challenges has been to assess the amount of mercury to which dental personnel have been exposed, preferably on an individual level. Studies of exposure levels in dental clinics have shown mostly low levels of mercury exposure, as indicated both by measured levels in the air at dental clinics and the urine of employees (8)(9)(10)(11). Such results have, however, been linked neither to short-nor long-term health effects.…”
mentioning
confidence: 99%